Emerging strategy towards mucosal healing in inflammatory bowel disease: what the future holds? - Wang, Min; Shi, Jingyan; Yu, Chao; Zhang, Xinyi; Xu, Gaoxin; Xu, Ziyan; Ma, Yong (Frontiers in Immunology, 2023)
For decades, the therapeutic goal of conventional treatment among inflammatory bowel disease (IBD) patients is alleviating exacerbations in acute phase, maintaining remission, reducing recurrence, preventing complications, and increasing quality of life. However, the persistent mucosal/submucosal inflammation tends to cause irreversible changes in the intestinal structure, which can barely be redressed by conventional treatment. In the late 1990s, monoclonal biologics, mainly anti-TNF (tumor necrosis factor) drugs, were proven significantly helpful in inhibiting mucosal inflammation and improving prognosis in clinical trials. Meanwhile, mucosal healing (MH), as a key endoscopic and histological measurement closely associated with the severity of symptoms, has been proposed as primary outcome measures. With deeper comprehension of the mucosal microenvironment, stem cell niche, and underlying mucosal repair mechanisms, diverse potential strategies apart from monoclonal antibodies have been arising or undergoing clinical trials. Herein, we elucidate key steps or targets during the course of MH and review some promising treatment strategies capable of promoting MH in IBD.